2018
DOI: 10.1111/jwas.12527
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Hot‐water Extract of Tropical Brown Seaweed, Sargassum cristaefolium, to Enhance Immune Response, Stress Tolerance, and Resistance of White Shrimp, Litopenaeus vannamei, to Vibrio parahaemolyticus

Abstract: The efficacy of hot-water extract of tropical brown seaweed, Sargassum cristaefolium (SCE), supplemented in diets on immune response, stress tolerance, and disease resistance of Litopenaeus vannamei to Vibrio parahaemolyticus was evaluated. Shrimp were fed diets containing graded levels of SCE (0, 250, 500, 750, and 1000 mg/kg). The results showed that shrimp fed all diets containing SCE had significantly higher (P < 0.05) immune response in total hemocyte count (THC), differential hemocyte count (granular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
1
5
0
5
Order By: Relevance
“…It is reported that the phagocytic activity of Fenneropenaeus indicus was higher in seawater containing brown algae (Sargassum glaucescens) [55]. Another study showed that the 11 Aquaculture Nutrition addition of S. cristaefolium to feed significantly enhanced the phagocytic activity of L. vannamei and effectively enhanced the disease resistance of white shrimp [49]. Similarly, in this experiment, the macroalgae diet significantly enhanced the phagocytic activity and expression of dynamin in L. vannamei compared to the control diet.…”
Section: Effects Of Macroalgaesupporting
confidence: 61%
See 1 more Smart Citation
“…It is reported that the phagocytic activity of Fenneropenaeus indicus was higher in seawater containing brown algae (Sargassum glaucescens) [55]. Another study showed that the 11 Aquaculture Nutrition addition of S. cristaefolium to feed significantly enhanced the phagocytic activity of L. vannamei and effectively enhanced the disease resistance of white shrimp [49]. Similarly, in this experiment, the macroalgae diet significantly enhanced the phagocytic activity and expression of dynamin in L. vannamei compared to the control diet.…”
Section: Effects Of Macroalgaesupporting
confidence: 61%
“…Cellular immunity is an essential part of the innate immunity of crustaceans and for defending against invading pathogens through phagocytosis, nodule formation, and encapsulation by hemocytes [48]. One study showed that supplementing brown algae (Sargassum cristaefolium) to basal feed significantly increased the THC of L. vannamei and enhanced resistance to ammonia stress [49]. Meanwhile, Niu et al also found that the supplementation of Porphyra haitanensis powder in the diet increased the THC of shrimps.…”
Section: Effects Of Macroalgaementioning
confidence: 99%
“…Immunostimulants from seaweed have been shown to increase the non-specific immunity of shrimp and fish. Hot-water Extract of Tropical Brown Seaweed, Sargassum cristaefolium, can increase Total Hemocyte Count (THC), Differential Hemocyte Count (granular and hyaline cells), and Phagocytic Activity in Litopenaeus vannamei and fight against Vibrio parahaemolyticus disease (Sudaryono et al, 2018). According to Zahra et al ., 2017 Sargassum sp. given by injection to tilapia increases leukocyte differential (lymphocytes, monocytes, neutrophils), Survival Rate (SR) to prevent Streptococciasis.…”
Section: Discussionmentioning
confidence: 99%
“…Rohmin et al (2017) mengungkapkan bahwa organisme patogen yang menghambat produksi budidaya udang diantaranya bakteri, virus, jamur dan parasiter. Organisme patogen, khususnya virus (Sudaryono et al, 2018b) dan bakteri (Sivagnanavelmurugan et al, 2012), yang menyerang budidaya udang dengan mudah menyebabkan kematian massal pada udang.…”
Section: Pendahuluanunclassified
“…Ketersediaan rumput laut di alam maupun produksi budidayanya yang melimpah menjadi kelebihan yang melekat padanya. Beberapa penelitian pada rumput laut, diketahui dapat meningkatkan sistem imun udang sehingga memengaruhi kelangsungan hidup organisme budidaya (Sivagnanavelmurugan et al, 2012;Sudaryono et al, 2018b;Schleder et al, 2017a).…”
Section: Pendahuluanunclassified